Regional Landslide Hazard and Risk Assessment Considering Landslide Spatial Aggregation and Hydrological Slope Units - Xuetao Yi; Yanjun Shang; He Meng; Qingsen Meng; Peng Shao; Izhar Ahmed (Applied Sciences)
Landslide risk assessment (LRA) is an important basis for disaster risk management. The widespread phenomenon of landslide spatial aggregation brings uncertainty to landslide hazard assessment (LHA) in LRA studies, but it is often overlooked. Based on the frequency ratio (FR) method, we proposed the dual-frequency ratio (DFR) method, which can quantitatively analyze the degree of landslide spatial aggregation. Using the analytic hierarchy process (AHP) and random forest (RF) models, we applied the DFR method to the LRA study of the Karakoram Highway section in China. According to the receiver operating characteristic (ROC) curve and the distribution characteristics of landslide hazard indices (LHIs), we evaluated the application effect of the DFR method. The results showed that the LHA models using the DFR method performed with higher accuracy and predicted more landslides in the zones with a high LHI. Moreover, the DFR-RF model had the best prediction performance, and its predictions were adopted together with vulnerability values to calculate the landslide risk. The zones with very high and high landslide risks were predominantly concentrated along highways in southern Aoyitake Town.